Analgesic Effect Test of Ethanol Extract of Kecipir Fruit (Psophocarpus tetragonolobus (L.) DC.) Against Male Mice with the Writhing Method - Fitri Nurhalimah; Fetri Lestari; Suwendar (Bandung Conference Series: Pharmacy, 2023)
Abstract. Pain, as a sensory perception, serves as an indicator of tissue damage, compromised nervous system functionality, or inflammation within the body. The objectives of this research encompassed the evaluation of analgesic activity exhibited by the ethanol extract derived from winged bean and the identification of the optimal dosage of the extract demonstrating analgesic properties in male mice. To achieve these goals, the experimental procedures involved the application of the writhing test. In this procedure, the writhing test was conducted to evaluate the peripheral analgesic activity. For this test, the mice were induced with 1% acetic acid (i.p), and the observed parameters encompassed the quantification of stretching behavior. The study comprised 6 (n=4) experimental groups: Group I served as the negative control and received 1% CMC Na. Group II acted as the positive control and was administered CMC Na along with the pain-inducing agent. Group III served as the comparison group, and the mice were administered paracetamol. Groups IV, V, and VI (Test doses 1,2, and 3) were given winged bean extract at doses of 250 mg/kg BB, 500 mg/kg BB, and 1000 mg/kg BB, respectively. The results unequivocally demonstrated the analgesic activity of the ethanol extract derived from winged bean fruit across all administered doses: 250 mg/kg BB, 500 mg/kg BB, and l000 mg/kg BB. Abstrak. Nyeri diartikan sebagai sensasi yang dirasakan untuk mengindikasikan bahwa sedang terjadinya kerusakan jaringan, tidak berfungsinya sistem saraf atau terjadinya inflamasi pada tubuh. Penelitian bertujuan untuk mengetahui aktivitas analgesik dari ekstrak etanol buah kecipir dan mengetahui dosis terbaik dari ekstrak etanol buah kecipir yang mempunyai aktivitas analgesik pada mencit jantan. Pengujian dilakukan dengan menggunakan metode writhing test, metode writhing test untuk menguji aktivitas analgesik perifer, mencit diinduksi asam asetat 1% (i.p) dengan parameter yang diamati berupa jumlah geliat, pengujian terdiri dari 6 (n=4) kelompok yaitu kelompok I (kontrol negatif) diberi CMC Na 1%, kelompok II (kontrol positif) diberi CMC Na dan induksi, kelompok III (pembanding) diberi parasetamol, kelompok IV, V dan VI (Dosis uji 1,2 dan 3) diberi ekstrak buah kecipir dengan dosis 250 mg/kg BB, 500 mg/kg BB dan 1000 mg/kg BB. Hasil menunjukkan bahwa ekstrak etanol buah kecipir memiliki aktivitas analgesik dengan dosis 250 mg/kg BB, 500 mg/kg BB dan 1000 mg/kg BB.